Perceptions of stalking: The influence of perpetrator mental disorder diagnosis, target-perpetrator gender, and perpetrator persistence - Landwehr, Ebonnie (2016)
Stalking is a complex phenomenon that results in significant harm to victims. For this reason, it is vital that knowledge and understanding of the behaviour be continually advanced. The aim of the present study was to investigate the influence of perpetrator mental disorder diagnosis, target-perpetrator gender, and persistence on perceptions of stalking. Although psychiatric diagnoses are prevalent among clinical stalker populations, little is known about how the presence of a perpetrator mental disorder may influence perceptions of stalking. Both target-perpetrator gender and persistence have been found to have an effect on perceptions of stalking, however it is not understood if or how the presence of mental disorder may interact with these factors. An experimental 2 × 2 × 2 independent factorial design was used to examine the influence of perpetrator mental disorder diagnosis, target-perpetrator gender, and perpetrator persistence on ascriptions of a stalking label, perceptions of behaviour seriousness and perceptions of responsibility. Two-hundred and eighty participants read one of eight vignettes and responded to one categorical item, five scale items, and an open-ended question pertaining to the behaviour described in the scenario. Overall, the majority of participants perceived the behaviour as stalking. Thematic analysis revealed that the repeated and unwanted nature of the behaviour and specific behaviours such as communicating with and following the target were of importance. Only mental disorder influenced ascriptions of a stalking label, with a chi-square analysis indicating that participants were significantly less likely to ascribe a stalking label in the presence of perpetrator mental disorder. Participants who did not ascribe a stalking label in the presence of mental disorder had concerns regarding the perpetrator’s responsibility for the behaviour. With regard to perceptions of behaviour seriousness and perceptions of responsibility, a MANOVA found significant main effects for mental disorder and target-perpetrator gender. A mentally disordered perpetrator was perceived as less responsible for their behaviour than a non-disordered perpetrator. Furthermore, in the presence of mental disorder, the target was perceived to be more responsible for encouraging the perpetrator’s behaviour. In regard to target-perpetrator gender, the behaviour was perceived to be more likely to result in violence and anxiety for the target when the vignette described a man pursuing a woman in comparison to a woman pursuing a man. When no psychiatric history was provided in the vignette, participants were asked to indicate how likely it was that the perpetrator had a mental disorder diagnosis. A MANCOVA including this covariate indicated that when mental disorder was assumed as opposed to stated, responsibility was not significant but behaviour seriousness was. The influence of a perpetrator’s mental disorder diagnosis and targetperpetrator gender on perceptions of stalking have implications for the treatment of perpetrators and victims, both informally and within the criminal justice system. It should be acknowledged that the discrepancy in findings between an explicitly stated and an assumed mental disorder diagnosis may be due to participants imagining different mental disorders, therefore future research should include the manipulation of diagnosis type